METODE PEKERJAAN CORE WALL PADA PROYEK TURYAPADA TOWER - Five, Johny; Sandjaya, Arif (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2024)
The study deals with the methods of implementation of the core wall work in the eight Turyapada Tower projects, using a holistic approach through field observations, interviewing executives, and field documentation. Implementation of the core wall begins with the foundations of the bore pile and the pile cap, then includes the core lift. The core wall and core lift are divided into 24 vertical segments. The segment 1 core wall bone is assembled in place, while the segment 2 core bone is mounted first and then connected to the segment 1. The process of segment 2 is repeated on the segment 3 which connects to segment 2 and so on to segment 24. Whereas the core lift bone for all segments is installed in place. The casting stage is 3 core wall segments and then 1 core lift segments. The advantages of bone installation and casting methods increase the efficiency of time and labor, while the disadvantages are difficult to put unassembled bone in place. The methods implemented can accelerate the work of the core wall of the Turyapada Tower project and can be an alternative to other project work methods. Abstrak Proyek pembangunan Turyapada Tower di Bali Utara memiliki tujuan besar untuk menjadi ikon Indonesia yang megah. Namun, proyek ini dihadapkan pada tantangan logistik yang signifikan terkait mobilitas alat dan material. Penelitian ini bertujuan untuk mengidentifikasi masalah mobilitas dan mengembangkan solusi efektif. Kendala utama meliputi keterbatasan ruang penyimpanan, pengelolaan logistik yang tidak efisien, dan pengaruh iklim ekstrim. Solusi termasuk optimalisasi rencana pengiriman, pemanfaatan ruang penyimpanan, pengawasan kelembaban, perawatan rutin, pemilihan kendaraan yang tepat, dan strategi distribusi yang lebih cerdas. Implementasi solusi ini telah menghasilkan peningkatan signifikan dalam mobilitas alat dan material, mengurangi risiko kerusakan material, meningkatkan efisiensi operasional, dan memastikan keamanan dalam proyek konstruksi Turyapada Tower.